2021
DOI: 10.1186/s12885-021-08668-w
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MCF2L-AS1 aggravates the malignant development of colorectal cancer via targeting miR-105-5p/RAB22A axis

Abstract: Background Colorectal cancer (CRC) represents one of the major malignant cancers in the world. It has been demonstrated that long non-coding RNAs (lncRNAs) can cause great influences on various human cancers. Though MCF.2 cell line derived transforming sequence like antisense RNA 1 (MCF2L-AS1) and its carcinogenic effect in CRC has been elucidated by several previous researches, the underlying mechanism remains unknown. Aim We aimed at exploring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Surprisingly, our research identified a significant decline in MCF2L-intronic-AS expression following surgery, which is identical to MCF2L-AS1 expression. Because potentially interact with the common proteins, MCF2L-intronic-AS may play a role in regulating the progression of CRC, which may include promoting cell proliferation, migration, invasion, epithelial-to-mesenchymal transition (EMT), and cell apoptosis ( 46 , 47 , 64 ). There are no studies that have reported the presence of MCF2L-intronic-AS in plasma; therefore, further investigations must be conducted to validate the dysregulation pattern of MCF2L-intronic-AS .…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, our research identified a significant decline in MCF2L-intronic-AS expression following surgery, which is identical to MCF2L-AS1 expression. Because potentially interact with the common proteins, MCF2L-intronic-AS may play a role in regulating the progression of CRC, which may include promoting cell proliferation, migration, invasion, epithelial-to-mesenchymal transition (EMT), and cell apoptosis ( 46 , 47 , 64 ). There are no studies that have reported the presence of MCF2L-intronic-AS in plasma; therefore, further investigations must be conducted to validate the dysregulation pattern of MCF2L-intronic-AS .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the aging-related lncRNAs included in this prognostic signature are closely linked to tumorigenesis, metastasis, and proliferation. MCF2L-AS1 promotes colorectal cancer development through the miR-105-5p/RAB 22A axis and regulates miR-873-5p levels to promote cancer stem-like features of non-small-cell lung carcinoma cells [28,29]. However, whether MCF2L-AS1 plays a role in BC has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…RAB22A, member RAS oncogene family (Rab22a) is another important tumor regulator[ 19 , 20 ], but its mechanism of action in AD is unclear. Its role in promoting neuroinflammation and oxidative stress[ 21 ] warrants the inclusion of Rab22a in the present study to explore its role in AD, especially since it affects Aβ accumulation[ 22 ].…”
Section: Introductionmentioning
confidence: 99%